International Production Cooperation Organizational Forms Typology and Reasoning for Approaches to Its Regulation - I. Sofishchenko; Ye. Kyrychenko (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The article investigates the features of economic and organizational forms of international industrial cooperation, in particular, the authors improved the typological approaches, summarized the experience of domestic enterprises integration into international industrial cooperation system, developed the approaches for encouraging domestic producers' interaction in the international cooperation relations, as well as provided recommendations on the criteria for analyzing the tools of cooperation assistance in state economic policy development. The generalization of economic and organizational features allowed to improve typological approaches to the classification of international industrial cooperation forms, as well as to determine the factors significantly affecting the international industrial cooperation development, suppressing or enhancing its effectiveness and functioning.